Observations and Modeling of a Hydrothermal Plume in Yellowstone Lake. Issue 12 (22nd June 2019) - Sohn, Robert A.; Luttrell, Karen; Shroyer, Emily; Stranne, Christian; Harris, Robert N.; Favorito, Julia E.
Abstract: Acoustic Doppler current profiler and conductivity‐temperature‐depth data acquired in Yellowstone Lake reveal the presence of a buoyant plume above the "Deep Hole" hydrothermal system, located southeast of Stevenson Island. Distributed venting in the ~200 × 200‐m hydrothermal field creates a plume with vertical velocities of ~10 cm/s in the mid‐water column. Salinity profiles indicate that during the period of strong summer stratification the plume rises to a neutral buoyancy horizon at ~45‐m depth, corresponding to a ~70‐m rise height, where it generates an anomaly of ~5% (−0.0014 psu) relative to background lake water. We simulate the plume with a numerical model and find that a heat flux of 28 MW reproduces the salinity and vertical velocity observations, corresponding to a mass flux of 1.4 × 10 3  kg/s. When observational uncertainties are considered, the heat flux could range between 20 to 50 MW. Key Points: Vertical velocity and conductivity‐temperature‐depth profiles reveal a hydrothermal plume in Yellowstone Lake The plume neutral buoyancy level is ~70 m above the lake floor, and vertical velocities of up to ~10 cm/s were observed in the mid‐water column We estimate the plume has a total heat flux of ~28 MW